2016
DOI: 10.1111/1467-9477.12080
|View full text |Cite
|
Sign up to set email alerts
|

Solid or Flexible? Social Trust from Early Adolescence to Young Adulthood

Abstract: The belief that people are generally fair and trustworthy has generated plenty of scholarly attention in recent decades, particularly in the Scandinavian countries, which are often known for high levels of social trust. This article draws attention to the current discussion in the literature on whether social trust is a stable cultural trait marked by persistence or is based on experiences and subject to change throughout life. Based on unique longitudinal data from five different cohorts of young people in Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Generally, two divergent perspectives in the literature have gained particular attention (Abdelzadeh & Lundberg, 2017;Bauer, 2014;Uslaner, 2008). The first is the cultural perspective, which implies that social trust is "part of an enduring culture" and thus a relatively "sticky" factor that becomes exceptionally stable over time (Dinesen, 2012;Uslaner, 2002).…”
Section: Divergent Perspectives On Social Trustmentioning
confidence: 99%
“…Generally, two divergent perspectives in the literature have gained particular attention (Abdelzadeh & Lundberg, 2017;Bauer, 2014;Uslaner, 2008). The first is the cultural perspective, which implies that social trust is "part of an enduring culture" and thus a relatively "sticky" factor that becomes exceptionally stable over time (Dinesen, 2012;Uslaner, 2002).…”
Section: Divergent Perspectives On Social Trustmentioning
confidence: 99%
“…The current study explored the role of the school while also considering other relevant explanations, thereby going beyond prior studies in the literature. In addition, previous studies often focused on tolerance among adults; in contrast, this study considered tolerance among adolescents, which is important as this represents a formative period for social and political attitudes (Lundberg & Abdelzadeh 2017a;Abdelzadeh & Lundberg, 2017). Finally, by controlling for various competing explanations and several background variables, the current study noted the importance of multiple factors besides the school that may influence tolerance.…”
Section: Resultsmentioning
confidence: 74%
“…They are in agreement with Flanagan and Stout (2010), who found that social trust was still dynamic among mid to late adolescents and was strongly related to respondents' sense of solidarity in school and opportunities to engage in free discussions. They also tally with Abdelzadeh and Lundberg (2017), who reported on a Swedish longitudinal study and also found generalized trust to be relatively volatile in early to mid-adolescence and to become more stable in early adulthood.…”
Section: Discussionmentioning
confidence: 75%